A Critical Look at Social and Territorial Impact: Intercultural Processes of Popular Innovation: A Critical Look at Social and Territorial Impact: Intercultural Processes of Popular Innovation - SANDOVAL FORERO, Eduardo; CAPERA FIGUEROA, José (Utopía y Praxis Latinoamericana, 2021)
In the current times, there is an urgent need to try out other forms of development that give weight to the traditional logics of thinking progress from the institutional streams, practices and speeches; that is, from the top down, which denotes the possibility of overcoming the political-bureaucratic schemes of procedural nature, which go against the forms of community organization that emerge in the territories where rural, ethnic and popular communities coexist. In this sense, the purpose of the following research article is to conceive the forms of communal organization as intercultural and decolonial experiences, which appeal to overcome the substantial differences that generate violence, to give way to the reconstruction of the social fabric from the practices, narratives and intersubjective processes of liberation from the individual and collective subject in the territory. This reflects upon the need to recognize the dynamics of social innovation from the feeling and need of peoples in movement for life, autonomy, culture and the emergence of peace from below.